Quasi-isometric cycling: A case study investigation of a novel method to augment peak power output in sprint cycling - Kordi, M.; Evans, M.; Howatson, G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Peak power output (PPO) is a determinant of sprint cycling performance and can be enhanced by resistance exercise that targets maximum strength. Conventional resistance training is not always suitable for elite cyclists because of chronic spinal issues; therefore, alternative methods to improve strength that concurrently reduce injury risk are welcome. In this case study, quasi-isometric cycling (QIC), a novel task-specific resistance-training method designed to improve PPO without the use of transitional resistance training, was investigated. Methods: A highly trained sprint track cyclist (10.401 s for 200 m) completed a 5-week training block followed by a second 5-week block that replaced conventional resistance training with the novel QIC training method. The replacement training method required the cyclist to maximally drive the crank of a modified cycle ergometer for 5 seconds as it passed through a ~100° range (starting at 45° from top dead center) at a constant angular velocity. Each session consisted of 3 sets of 6 repetitions on each leg. The lab PPO was recorded in the saddle and out of the saddle. Results: Conventional training did not alter sprinting ability; however, the intervention improved the out-of-the-saddle PPO by 100 W (from 1751 to 1851 W), while the in-the-saddle PPO increased by 57 W from 1671 to 1728 W. Conclusion: QIC increased PPO in a highly trained, national-level sprint cyclist, which could be translated to improvements in performance on the track. Furthermore, QIC provides a simple, but nonetheless effective, alternative for sprint track cyclists who have compromised function to perform traditional strength training.